MUSIC COLLOQUIUM - The Star, (2012)
The Music Department of Universiti Putra Malaysia (UPM) will be having an International Colloquium on Music Research 2012 from May 3 till today at the Faculty of Human Ecology in UPM,Seri Kembangan.